Correlation of humoral immunity to Pasteurella multocida in ducks and passive mouse protection - RAMANATHA, K R (The Indian Journal of Animal Sciences, 2013)
Correlation-regression analysis was made between humoral antibody levels against crude capsular polysaccharide antigen tested by indirect haemagglutination (IHA) test on duck sera collected after vaccination with Pasteurella multocida A: 1 vaccine and the rates of passive protection of mice againsthomologous challenge with 50 LD50 (716 viable cells). The rates of protection of mice by sera collected from ducks before vaccination, 94 days after 1 vaccination and 70 days after 2 vaccinations were, respectively, 1/20 (5%), 7 /8 (87.5%) and 8/8 (100%) for pooled sera and 3/44 (6.82%), 13/18 (72.22%) and 16/19 (84.21 %) for individual sera. The IHA titres were significantly higher for vaccinated over unvaccinated, and for twice vaccinated over once vaccinated ducks. There was a significantly high correlation betwccn IHA Litres and rates of protection of mice.